Membaca Konflik: Problematika dan Refleksi atas Kehidupan Beragama Masyarakat Aceh Singkil - Prasetiya, *Angga; Persada, Soma Surya (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2022)
Aceh is a region in Indonesia that implements a special autonomy policy based on Islamic law. In that special autonomy, one of the things that are regulated is the freedom of religion that has been enshrined in the qanun. Qanun is a local regulation that regulates the government and lives of people in Aceh Province. In the qanun, the religious freedom of the people of Aceh has been guaranteed and protected. However, there are some conflicts between religious groups that have the potential to cause disharmony. One such region is Singkil. This article aims to describe the problems and reflections on the religious life of the people of Aceh Singkil. The research method used in this study is qualitative with a literary study approach. The results showed that there are factors that encourage the emergence of conflicts, namely the lack of tolerance and cynicism toward a difference in society. Therefore, it is necessary to realize inclusive community attitudes and strengthen the literacy of moderation of religious life through various humanist approaches. In addition, a firm attitude of the government is needed in setting a fair policy that accommodates all groups.